Penerapan Good Governance dan Pengendalian Internal dalam Meningkatkan Kinerja Pengelolaan Keuangan di Polrestabes Palembang - Tania; Fitriasuri (As-Syirkah: Islamic Economic & Financial Journal, 2025)
The implementation of the concept of Good Governance and a systematic internal control framework is expected to improve the performance of financial management in the Palembang Police environment. Although various provisions and guidelines on Good Governance and SPIP have been available, findings in the field still found various obstacles related to consistency of implementation, transparency of information, accountability, synergy between units, and optimal use of information technology. "These obstacles can reduce the effectiveness of management and increase the possibility of deviations. This study uses a survey methodology with 54 respondents, with data collection through questionnaires and evaluation using multiple linear regression to assess the impact of each variable. The results of this study aim to refine the theoretical framework and practical applications, so that they can enrich academic literature and provide policy suggestions in order to improve financial governance in the Palembang Police environment. Improving human resource competence, internalizing the ideals of integrity, and establishing a consistent supervisory framework are essential to realizing a professional, transparent, and responsible police institution in the future.